Challenges of Exporting Differentiated Products to Developed Countries: The Case of SME-Dominated Sectors in a Semi-Industrialized Country - Alejandro Artopoulos; Daniel Friel; Juan Carlos Hallak (Inter-American Development Bank (IDB), 2010)
This paper surveys four Argentinean industrieslight ships, television programs, wines, and wooden furniturethat have experienced substantial export growth in recent years, particularly to developed countries. The case studies first describe the structure of the industries, then characterize the emergence of export pioneers and the subsequent process of diffusion. Finally, they analyze the role played by public institutions. Across sectors, the appearance of a pioneer is largely explained by a knowledge advantage relative to other industry participants regarding foreign markets, which the pioneer acquired previously and independently of his decision to export. Diffusion occurs across as well as within sectors, as pioneers knowledge is relevant to other industries. Since diffusion does not necessarily hurt the pioneer, public policy has a potentially important role in fostering diffusion within and across sectors.
Keywords: L62; L66; L68; L82; 330; Small and Medium Enterprises; Exports; Argentina